Early Coronary Reperfusion Facilitates Return of Spontaneous Circulation and Improves Cardiovascular Outcomes After Ischemic Cardiac Arrest and Extracorporeal Resuscitation in Pigs - Alice Hutin; Lionel Lamhaut; Fanny Lidouren; Matthias Kohlhauer; Nicolas Mongardon; Pierre Carli; Alain Berdeaux; Bijan Ghaleh; Renaud Tissier (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Extracorporeal cardiopulmonary resuscitation (ECPR) is widely proposed for the treatment of refractory cardiac arrest. It should be associated with coronary angiography if coronary artery disease is suspected. However, the prioritization of care remains unclear in this situation. Our goal was to determine whether coronary reperfusion should be instituted as soon as possible in such situations in a pig model. Methods and Results Anesthetized pigs were instrumented and submitted to coronary artery occlusion and ventricular fibrillation. After 5 minutes of untreated cardiac arrest, conventional cardiopulmonary resuscitation (CPR) was started. Fifteen minutes later, ECPR was initiated for a total duration of 240 minutes. Animals randomly underwent either early or late coronary reperfusion at 20 or 120 minutes of ECPR, respectively. This timing was adapted to the kinetic of infarct extension in pigs. Return of spontaneous circulation was determined as organized electrocardiogram rhythm with systolic arterial pressure above 80 mm Hg. During conventional CPR, hemodynamic parameters were not different between groups. Carotid blood flow then increased by 70% after the onset of ECPR in both groups. No animal (0 of 7) elicited return of spontaneous circulation after late reperfusion versus 4 of 7 after early reperfusion (P=0.025). The hemodynamic parameters, such as carotid blood flow, were also improved in early versus late reperfusion groups (113±20 vs 43±17 mL/min after 240 minutes of ECPR, respectively; P=0.030), along with infarct size decrease (71±4% vs 84±2% of the risk zone, respectively; P=0.013). Conclusions Early reperfusion improved hemodynamic status and facilitated return of spontaneous circulation in a porcine model of ischemic cardiac arrest treated by ECPR.